Experimental and Numerical Study on the Impact of Air Gaps Between Layers on the Ballistic Performance of Steel-Rubber Laminated Composites - Bakri, Bakri; Muhammad Syaiful Fadly,; Anwar, Khairil; Chandrabakty, Sri; Ricsen, (International Journal of Integrated Engineering, 2025)
Laminated steel–rubber composites are widely recognized for their capability to absorb and dissipate impact energy, making them promising candidates for ballistic protection. Despite their potential, the specific role of internal air gaps in influencing ballistic resistance has not been thoroughly explored. This research focuses on assessing how different air gap configurations affect the protective performance of these layered composites. A series of ballistic tests were carried out using 9 mm caliber hemispherical projectiles, supported by finite element simulations to replicate and validate the observed behaviors. Tests were conducted on specimens with varying air gaps between layers, including a configuration without any gap. The lowest penetration depth was observed in the specimen with no air gap, registering 6.502 mm in the experimental data and 6.885 mm in the simulation. Conversely, the highest penetration was recorded in the 3 mm air gap setup, reaching 10.357 mm and 10.092 mm for experimental and simulation results, respectively. Interestingly, the 2 mm air gap condition exhibited a notable rise in projectile kinetic energy, peaking at 547.6 J at 9.175 × 10⁻⁵ seconds, which then stabilized. These findings indicate that although greater air gaps allow deeper projectile intrusion, they effectively prevent back plate damage by concentrating stress absorption on the front layers. Overall, the study demonstrates that air gap design plays a critical role in controlling energy distribution and enhancing the impact resistance of steel–rubber composites.